Principles in power: Latin America and the politics of U.S. human rights diplomacy - Walker, Vanessa (The United States in the world, 2020)
"In the 1970s human rights advocates and U.S. government officials created a uniquely anti-interventionist, self-critical human rights agenda in Latin America and beyond. This book exposes the strained yet transformative relationship between these ambivalent allies"--